Strength and heat emissions performance of high strength concrete containing fine metakaolin & palm oil fuel ash as partial cement replacement - Abu Bakar, M. N. R.; Ismail, M. H.; Che Rahim, N. A. N.; Majid, M. A.; Md Noor, N.; George, A. F. (2024)
Cement production significantly contributes to greenhouse gas emissions, specifically carbon dioxide (CO2). In addition to the CO2 emissions from cement production, the increase in palm oil fuel ash (POFA), which is the by-product of the palm oil industry, can also contribute to environmental pollution. This study carried out on POFA and metakaolin (MK) as a partial cement replacement can reduce the problem of greenhouse and environmental effects. Apart from that, it can also increase the level of concrete strength. The slump and compressive strength tests were carried out first on concrete that uses fine metakaolin (FMK) only as a partial cement replacement to obtain an optimum value of FMK. Thus, the optimum FMK content found in this study was 20%. Next, slump tests, compressive strength tests, and heat of hydration tests were carried out on samples containing FMK and POFA content as a partial cement replacement up to 40% of the total cement replacement. The POFA content starts at 5%, followed by 10%, 15%, and 20%. In addition to that, FMK content of 20% and superplasticizer (SP) of 2% were constant for all design mixes. The workability of concrete decreases with the inclusion of FMK and POFA as partial cement replacements and 2% of SP as a constant. However, the strength of concrete containing 20% FMK and 5% POFA as partial cement replacement has given better compressive strength than ordinary Portland cement (OPC) concrete up to 14.07% at 28 days. Additionally, it is found that the exact amount of 20% FMK and 5% POFA enables concrete to be reduced to 5.54% in peak temperature compared to OPC concrete. Furthermore, the formation of C-S-H gel was increasingly generated and able to fill in the gaps in concrete when the POFA content increased, thus making the concrete denser and stronger than the control series.